Ultrafast laser writing of liquid crystal waveguides - Chen, B; Xie, P; Zhao, Z; Salter, PS; Li, M; Xue, L; Qiu, X; Booth, MJ; Elston, SJ; Morris, SM (American Association for the Advancement of Science, 2024)
With the development of conformable photonic platforms, particularly those that could be interfaced with the human body or integrated into wearable technology, there is an ever-increasing need for mechanically flexible optical photonic elements in soft materials. Here, we realize mechanically flexible liquid crystal (LC) waveguides using a combination of ultrafast direct laser writing and ultraviolet (UV) photo-polymerization. Results are presented that demonstrate that these laser-written waveguides can be either electrically switchable (by omitting the bulk UV polymerization step) or mechanically flexible. Characteristics of the waveguide are investigated for different fabrication conditions and geometrical configurations, including the dimensions of the waveguide and laser writing power. Our findings reveal that smaller waveguide geometries result in reduced intensity attenuation. Specifically, for a 10-μm-wide laser-written channel in a 14-μm-thick LC layer, a loss factor of −1.8 dB/mm at λ = 650 nm was observed. Following the UV polymerization step and subsequent delamination of the glass substrates, we demonstrate a free-standing flexible LC waveguide, which retains waveguide functionality even when bent, making it potentially suitable for on-skin sensors and other photonic devices that could interface with the human body. For the flexible LC waveguides fabricated in this study, the loss in a straight waveguide with a cross-sectional area of 20 μm × 20 μm was recorded to be −0.2 dB/mm. These results highlight the promising potential of electrically responsive and mechanically moldable optical waveguides using laser writing and UV-assisted polymer network formation.